Encapsulation of industrial solid waste / Ku Halim Ku Hamid and Rosmawati Abdul Aziz - Ku Hamid, Ku Halim; Abdul Aziz, Rosmawati (2002)
Local industries produce a large amount of sludge and solid waste from their production processes. This phenomenon created a disposal problem and managing of these waste materials become one of the major environmental and economical issues. The purpose of this study is to evaluate and develop a treatment method using these wastes to a useful product. The characteristic and constituent of some industrial wastes used in this study were analyzed before the treatment. Suitable ingredients such as magnesite material and proprietary additive (KH1 and KH2) were used to solidify the wastes and optimum ratios of the ingredients were determined to form a concrete-like mass. Strength and leachability tests were conducted on the treated wastes. The finding of this investigation revealed that the solidified waste could be recycled into a useful product using encapsulation technique.